Perilaku Pedagang Muslim di Pasar Tradisional (Pendekatan Induktif dalam Pembentukan Teori Produksi Ekonomi Islam) - Marlina (Departement of Sharia Economics, Faculty of Islamic Economics and Business, IAIN Pekalongan, 2022)
This article attempts to describe two academic problems. First, how the motives and behavior of Muslim traders in traditional markets. Second, how these motives and behaviors are related to the theorizing of Islamic Economics, especially in the theory of production. This field research is a qualitative-phenomenological approach, using a descriptive-verificative type. Data were obtained directly from traditional market traders in four markets, namely Pasar Anyar and Banjarsari (urban areas) and Pasar Warungasem and Tersono (rural). The research used purposive sampling, while the validity and credibility of the data used triangulation, emic, and member-checking techniques. Data analysis was conducted inductively with domain analysis. The study developed two research findings. First, the behavior motive of traders is to fulfill material needs, however, their behavior in the market is attached to religious ​​and social values. Second, the reasons and behavior of Muslim traders strengthen the scientific theorization of Islamic Economics, because their behavior that is included in the inductive-empirical-profane realm has conformity with other sources in the theorizing process, namely sources from the deductive-abstract-universal-transcendent domain